Fertility changes in Latin America in the context of economic uncertainty - Alicia Adsera; Alicia Menendez (Institute for the Study of Labor (IZA), 2009)
We explore the relation between fertility and the business cycle in Latin American countries taking advantage of the existing cross-country and within-country differences in both fertility and macroeconomic conditions. First, we use a panel of 18 nations for over 45 years to study how different labor market and economic shocks may have affected fertility. Second, we estimate Cox proportional hazard models of transitions to 1st, 2nd, and 3rd births with individual Demographic and Health Survey data from ten countries. We find that periods of relative high unemployment are associated with lower fertility and with relative postponements of maternity (and to some extent second and third births). In general, women seem to postpone and even reduce childbearing in response to downturns. This behavior is mainly associated to increasing unemployment rather than slowdowns in GPD growth, although we find a positive relationship between first births and growth. Despite that periods of unemployment may be good to have children because opportunity costs are lower, maternity is reduced or postponed, in particular, among the most recent cohort and among urban and more educated women. This is consistent with the idea that, in this context, income effects are dominant.
urn:nbn:de:101:1-20090304764
Keywords: J13; J16; 330; Latin America; unemployment; fertility; growth; Fruchtbarkeit; Arbeitslosigkeit; Konjunktur; Wirtschaftswachstum; Risiko; Lateinamerika